Hierarchically Oriented Jellyfish‐Like Gold Nanowires Film for Elastronics. (14th November 2022) - Zhang, Heng; Lin, Fenge; Cheng, Wenlong; Chen, Yi; Gu, Ning
Abstract: Stretchable electronics (i.e., Elastronics) are essential to the realization of next‐generation wearable bioelectronics for personalized medicine, due to their unique skin‐conformal features ideal for seamless integration with the human body. Significant progress has been made to nanowire‐based elastronics with promising applications ranging from electronic‐skin to advanced energy harvest systems. However, it remains a key challenge to rationally control over the nanowire morphology and configurations to achieve desired multifunctionality. Herein, a stretchable jellyfish‐like gold nanowires film with high conductivity and stretchability is presented by using gold nanostar‐seeded nanowire growth method. They exhibit unique hierarchically oriented structure with gold nanostars as the multi‐branched active sites (top layer) and vertically intertwined nanowires (bottom layer) trailing below the nanostars. Such nanowires film can be stretched up to 200% with a retaining low normalized resistance of 13.8 due to the unique hierarchical structure. Furthermore, the film can be used as stretchable supercapacitor with a 92% capacitance retention and superior durability even after 5000 electrochemical scanning cycles. The method is general, which can be further expanded to other metallic seeds, hence, representing a low‐cost yet efficient strategy for the fabrication of stretchable elastronics and robust energy storage devices for on‐body biosensing and bioelectronics. Abstract : Hierarchically oriented jellyfish‐like gold nanowires films with high conductivity and stretchability are fabricated by using gold nanostar seeded nanowire growth method. The hierarchical structure and mechanical robustness lead to excellent capacitive performances, long cycle stability, and superior stretchability, which pave versatile and efficient avenue for stretchable elastronics and skin‐compatible energy storage devices with potential applications in on‐body biosensing and bioelectronics.